Type and Strategy of Code Switching Used by English Teachers in The Process of Teaching and Learning English - julian chandra; Siska Oktawidya Wati (Jurnal Ilmiah Langue and Parole, 2021)
The purpose of this research were: (1) to describe type of using code switching and (2) to describe the strategy behind the use code switching made by English teachers in English language teaching and learning at SMAN 1 Padang Sago. This research used descriptive qualitative design. The population were all English teachers in the school who taught English subject for 10th, 11th and 12 th graders in the 2019 academic year . The purposive sampling technique was employed in the research in which the total sampling were all 5 English teachers. Instrumens to collect the data were observation chceklist and interview. In the observation checklist, all teachers’ utterancess were categorized according to the types and strategies of the code switching belong to. To determine the frequency of the type and strategy of the code switching emerging in observation checklist, the numberof the type and strategy that emerged were count manulay. Then, the percentage formula was used. Then, the interview was used to validate the result gained from the observation checklist. Finally, among 110 utterances , it was found there was 4%, of tag switching used by the tecaher, inter-sentential switching was 36%, and intra-sentential switching was 60%,. On the other hand, among 10 strategies of code switching proposed by Hoffman (1991), it was found that the teacher preferred to use only 4 strategies only of which are for scosiisted of expressing solidarity 48%, interjection7%, repetition 28%, and clarification19%).